Econometric contributions to public policy : proceedings of a conference held by the International Economic Association at Urbino, Italy - Stone, Richard; Peterson, William; International Economic Association (New York : St. Martin's Press, 1978)
The papers in this volume, are grouped under three broad headings: Econometric Models and Economic policy; Income Distribution, Welfare and Taxation; and Regional , Environmental and Social Policy.
Includes bibliographical references and index.
rpm 13/07/2017
Loans
Keywords: Economic policy; Welfare economics; Econometrics